CD40/CD40L expression and its prognostic value in cervical cancer - G.A. Grazia; D.R. Bastos; L.L. Villa (Brazilian Journal of Medical and Biological Research, 2023)
CD40, a member of the tumor necrosis factor receptor (TNFR) family, is known to be involved in immune system regulation, acting as a costimulatory molecule, and in antitumor responses against cancer cells. It is a protein that is expressed in different types of cells, including immune cells and cancer cells (e.g., cervical cancer, breast cancer, melanoma). In this study, we investigated CD40/CD40L transcriptional and protein levels in cervical cancer cell lines and tumors. Higher CD40 expression was observed in cervical cancer cell lines derived from squamous cell carcinomas than from adenocarcinomas. Search of CD40/CD40L expression in cervical cancer tissues in public data sets revealed that about 83% of squamous cell carcinomas express CD40 compared to other cervical tumor subtypes. Moreover, expression of CD40 and CD40L in squamous cervical carcinomas is associated with better overall survival. Therefore, these proteins could be explored as prognostic markers in cervical cancers.